Investigating Nonspecific Effects of the Live-Attenuated Japanese Encephalitis Vaccine on Lower Respiratory Tract Infections in Children Aged 25-35 Months: Retrospective Cohort Study - Siyi Zhan; Hongbo Lin; Yingying Yang; Tao Chen; Sheng Mao; Chuanxi Fu (JMIR Publications, 2024)
BackgroundLive attenuated vaccines may be used to prevent nontargeted diseases such as lower respiratory tract infections (LRTIs) due to their nonspecific effects (NSEs). ObjectiveWe aimed to analyze the NSEs of the Japanese encephalitis vaccine on pediatric LRTIs in children aged 25 months to 35 months. MethodsA retrospective cohort study was conducted by using a population-based electronic health record database in Zhejiang, China. Enrolled participants were children born from January 1, 2017, to December 31, 2017, and who were inoculated with the live-attenuated Japanese encephalitis vaccine (JE-L) or inactivated Japanese encephalitis vaccine (JE-I) as the most recent vaccine at 24 months of age. The study was carried out between January 1, 2019, and December 31, 2019. All inpatient and outpatient hospital visits for LRTIs among children aged 25 months to 35 months were recorded. The Andersen-Gill model was used to assess the NSEs of JE-L against LRTIs in children and compared with those of JE-I as the most recent vaccine. ResultsA total of 810 children born in 2017 were enrolled, of whom 585 received JE-L (JE-L cohort) and 225 received JE-I (JE-I cohort) as their last vaccine. The JE-L cohort showed a reduced risk of LRTIs (adjusted hazard ratio [aHR] 0.537, 95% CI 0.416-0.693), including pneumonia (aHR 0.501, 95% CI 0.393-0.638) and acute bronchitis (aHR 0.525, 95% CI 0.396-0.698) at 25 months to 35 months of age. The NSEs provided by JE-L were especially pronounced in female children (aHR 0.305, 95% CI 0.198-0.469) and children without chronic diseases (aHR 0.553, 95% CI 0.420-0.729), without siblings (aHR 0.361, 95% CI 0.255-0.511), with more than 30 inpatient and outpatient hospital visits prior to 24 months of age (aHR 0.163, 95% CI 0.091-0.290), or with 5 to 10 inpatient and outpatient hospital visits due to infectious diseases prior to 24 months old (aHR 0.058, 95% CI 0.017-0.202). ConclusionsCompared with JE-I, receiving JE-L as the most recent vaccine was associated with lower risk of inpatient and outpatient hospital visits for LRTIs among children aged 25 months to 35 months. The nature of NSEs induced by JE-L should be considered for policymakers and physicians when recommending JE vaccines to those at high risk of infection from the Japanese encephalitis virus.